Glucose sensor based on nanostructured carbon electrode with immobilized PQQ-containing glucose dehydrogenase: Construction, experimental study and mathematical modeling - Puida, Mantas; Dabulytė - Bagdonavičienė, Jurgita; Ivanauskas, Feliksas; Razumas, Valdemaras; Razumienė, Julija; Šakinytė, Ieva (Nonlinear Analysis: Modelling and Control, 2019)
Oxidized graphite (OG) has been prepared by carrying out the synthesis of graphene in the alkaline media using K3[Fe(CN)6] as the oxidizing agent. This synthesis protocol allowed us to obtain and further to apply the OG as an effective electrode material for the reagentless enzyme electrode in which electron transfer between electrode and enzyme active site proceeds directly, without any additional mediators. Direct electron transfer in this bioelectrocatalytic system has been achieved from the active site of pyrroloquinoline quinone-containing glucose dehydrogenase (PQQ-GDH) to the nanostructurized carbon electrode surface. The numerical modeling of biosensor made possible to determine several structural and kinetic parameters of the sensor constructed. Our model of PQQ-GDH-based biosensor is built under three main assumptions. First, we assume that the electron transfer between enzyme active center and OG proceeds via the electron hopping mechanism, and therefore the rate of this reaction depends on the diffusion coefficient of an electron in OG layer. Second, enzyme is immobilized, and its diffusion coefficient is assumed to be zero. Finally, after the reaction with substrate, enzyme needs to be regenerated by the oxidized functionalities of OG.
Keywords: oxidized graphite; biosensor; PQQ-GDH; immobilized enzyme; mathematical modeling